A longitudinal investigation into cognition and disease progression in spinocerebellar ataxia types 1, 2, 3, 6, and 7. Issue 1 (December 2016) - Moriarty, Amy; Cook, Arron; Hunt, Helen; Adams, Matthew; Cipolotti, Lisa; Giunti, Paola
Abstract Background The natural history of clinical symptoms in the spinocerebellar ataxias (SCA)s has been well characterised. However there is little longitudinal data comparing cognitive changes in the most common SCA subtypes over time. The present study provides a preliminary longitudinal characterisation of the clinical and cognitive profiles in patients with SCA1, SCA2, SCA3, SCA6 and SCA7, with the aim of elucidating the role of the cerebellum in cognition. Methods 13 patients with different SCAs all caused by CAG repeat expansion (SCA1, n = 2; SCA2, n = 2; SCA3, n = 2; SCA6, n = 4; and SCA7, n = 3) completed a comprehensive battery of cognitive and mood assessments at two time points, a mean of 7.35 years apart. All patients were evaluated clinically using the Scale for the Rating and Assessment of Ataxia (SARA) and the Inventory of Non-Ataxia Signs (INAS). Patients underwent structural MRI imaging at follow-up. Results Clinical scale scores increased in all patients over time, most prominently in the SCA1 (SARA) and SCA3 (INAS) groups. New impairments on neuropsychological tests were most commonly observed with executive functions, speed, attention, visual memory and Theory of Mind. Results suggest possible differences in cognitive decline in SCA subtypes, with the most rapid cognitive decline observed in the SCA1 patients, and the least in the SCA6 patients, congruent with observed patterns of motor deterioration. Minimal changes in mood were observed, and MRI measures of atrophy did not correlate with cognitive decline. Conclusion As well as increasing physical impairment, cognitive decline over time appears to be a distinct aspect of the SCA phenotype, in keeping with the cerebellar cognitive-affective syndrome. Our data suggest a trend of cognitive decline that is different for each SCA subtype, and for the majority is related to the severity of cerebellar motor impairment.